Evaluation of the core thickness and resin cement on the fracture strength of zirconia-based multilayer computer-aided design/computer-aided manufacturing ceramic crowns - Idris Kavut; Safak Külünk (Dentistry and Medical Research, 2019)
Aim: The purpose of this study was to evaluate the effect of thickness of zirconia core and different resin cements on the fracture strength of veneered zirconia crowns designed by multilayer technique. Materials and Methods: Forty metal dies were constructed to replica maxillary molar. Forty zirconia cores (Sirona inCoris ZI) were designed and constructed (inLab 4.4) with different thicknesses. The thickness of zirconia core was selected as 0.5 and 0.7 mm. Forty Feldspathic ceramic (VITABLOCS Mark II) veneers were fabricated (inLab 4.4) onto the zirconia cores. The zirconia cores were divided into two subgroups, and veneers were cemented with one of the following resin cement: self-cure, self-adhesive resin cement with light-cured option (Multilink N), and a dual-cure resin cement (Panavia F 2.0). Then, crowns were cemented to the metal dies. All the specimens were subjected to thermal cycling 5000 times (5°C–55°C ± 2°C, immersion time: 30 s). A universal testing machine was used for fracture strength test at a crosshead speed of 1 mm/min. The data were analyzed with one-way analysis of variance (α = 0.05). Stereomicroscopy was used to evaluate the failure modes and surface structure. Results: Zirconia core thickness and resin cement material affected the fracture strength (P < 0.05). Increase in core thickness increased the fracture strength of multilayer veneer crown (P < 0.05). Higher fracture strength values were obtained with light-cured, self-adhesive cement in both core thicknesses. Conclusion: Although 0.5-mm thickness zirconia cores showed lower flexural strength, it was higher than the maximum loads which may occur clinically (Fmax= 600 N on one tooth). Furthermore, light-cured, self-adhesive resin cement is advisable to increase the fracture strength with different core thickness.